2020
DOI: 10.3390/atmos11101103
|View full text |Cite
|
Sign up to set email alerts
|

The Ångström Exponent and Single-Scattering Albedo of Black Carbon: Effects of Different Coating Materials

Abstract: In this work, the absorption Ångström exponent (AAE), extinction Ångström exponent (EAE), and single-scattering albedo (SSA) of black carbon (BC) with different coating materials are numerically investigated. BC with different coating materials can provide explanations for the small AAE, small EAE ,and large AAE observed in the atmosphere, which is difficult to be explained by bare BC aggregate models. The addition of organic carbon (OC) does not necessarily increase AAE due to the transformation of BC morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 105 publications
(197 reference statements)
1
12
0
Order By: Relevance
“…In this work, R c = 50R g and R c = R g were assumed to represent the film and spherical coatings and are named Model B and Model C, respectively. In our previous study (Luo et al, 2019), we have demonstrated that our proposed models can greatly simulate the internally mixed BC morphologies and reproduce the measured absorption as well. For more details about the algorithm to generate the coated BC, please refer to Luo et al (2019), and the typically generated morphologies are shown in Fig.…”
Section: Morphologiesmentioning
confidence: 71%
See 4 more Smart Citations
“…In this work, R c = 50R g and R c = R g were assumed to represent the film and spherical coatings and are named Model B and Model C, respectively. In our previous study (Luo et al, 2019), we have demonstrated that our proposed models can greatly simulate the internally mixed BC morphologies and reproduce the measured absorption as well. For more details about the algorithm to generate the coated BC, please refer to Luo et al (2019), and the typically generated morphologies are shown in Fig.…”
Section: Morphologiesmentioning
confidence: 71%
“…Non-spherical aerosol models show more excellent performance on reproducing the measurements even though the Mie theory was commonly used in remote sensing and climate modeling (Bi et al, 2018;He et al, 2016He et al, , 2015Chakrabarty et al, 2007;Luo et al, 2019). In the atmosphere, BC can be mixed with BrC, and the mixing states are commonly divided into externally mixed and internally mixed.…”
Section: Morphologiesmentioning
confidence: 99%
See 3 more Smart Citations